LINGUOPRAGMATIC FEATURES OF METAPHOR AND METONYMY IN THE TRANSLATION OF PUBLICISTIC TEXTS (BASED ON ENGLISH AND UZBEK MATERIALS) - Gafurova Gulrukh Bakhtiyarovna (International Scientific and Current Research Conferences, 2026)
This paper analyzes the linguostylistic and pragmatic features of metaphor and metonymy in the translation of publicist texts. The research is conducted on the basis of English and Uzbek language materials and examines the role of these stylistic devices in ensuring textual expressiveness as well as the problems of their adequate rendering in translation. The study substantiates the necessity of preserving not only semantic equivalence but also pragmatic equivalence in the translation process.